Gastro-tourism marketing’s impact on Indonesia’s nation brand image among Pakistani Gen Z - Ade Pranajaya; Sara Rashid (Universitas Pendidikan Nasional, 2026)
The study examines how Gastronomy and Tourism Diplomacy, as a global marketing strategy, influences Indonesia's nation brand in Pakistan, with Pakistani Gen Z’s cross-cultural understanding (CCU) acting as a mediator. Using a quantitative approach, 545 responses were collected through purposive sampling to target respondents aligned with the research objectives, and Structural Equation Modeling (SEM) was applied for analysis. The findings reveal that gastronomy and tourism diplomacy strategies do not directly enhance Indonesia’s nation brand image among Pakistani Gen Z; instead, their influence operates indirectly through CCU, which significantly strengthens brand perceptions. These results suggest that effective nation branding depends on culturally immersive initiatives that foster familiarity and deeper cognitive engagement. Practically, this implies that policymakers and tourism marketers should prioritize programs such as cultural exchange campaigns, localized culinary promotions, and interactive digital storytelling to enhance cross-cultural understanding among target audiences. By embedding cultural meaning into promotional strategies, governments and tourism stakeholders can improve the effectiveness of diplomacy efforts and build more favorable international perceptions. This research underscores the importance of cultural engagement in shaping nation brand evaluations, demonstrating that diplomacy-driven marketing is more impactful when it actively cultivates cross-cultural understanding among younger generations.